Phytochemical screening and antioxidant activity of Psidium guajava - Jani, Nor Akmalazura; Ahmad Azizi, Nurul Alia; Aminudin, Nurul Iman (2018)
Psidium guajava or commonly known as guava is useful to treat gastroenteritis, dysentery, stomach pain and indigestion. The leaves of P. guajava was screened for phytochemical and antioxidant activity. The phytochemicals were extracted by sequential maceration using n-hexane, chloroform and methanol, while phytochemical screening was performed using various chemical tests. Antioxidant activity was assessed by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. Steroids and terpenoids were present in the n-hexane extract, while phenols and terpenoids were detected in the chloroform extract. The methanol extract was found to contain flavonoids, steroids, saponins, phenols and terpenoids. Among the tested extracts, the methanolic extract demonstrated strong DPPH radical scavenging activity with an IC50 value of 51.07 µg/mL.